Budgetary Subsidies in Centrally Planned Economies in Transition - Holzmann, Robert (IMF Working Papers; Working Paper ;, 1991)
This paper analyzes budgetary subsidy policy issues that arise when centrally planned economies move toward a market economy. The analysis suggests that subsidy reduction, to be successful, has to be embedded into an overall economic reform program and that during the program's execution, former implicit subsidies are likely to become budgetized. Furthermore, additional pressure on the budget, caused by enterprise restructuring or the introduction of social safety net provisions, necessitates careful policy design. Comprehensive budgetary reform is required to prevent budgetary slippages during the transition process.